A Computationally Efficient Coupled Electrochemical-Thermal Model for Large Format Cylindrical Lithium Ion Batteries. Issue 13 (1st January 2019) - Tran, Ngoc Tham; Farrell, Troy; Vilathgamuwa, Mahinda; Choi, San Shing; Li, Yang
Abstract : We present a one-dimensional, radial, coupled degradation-electrochemical-thermal (DET) model of a large format cylindrical lithium ion cell. The model consists of reduced order equations that describe the electrochemical phenomena, including that associated with degradation, coupled with an approximate model of thermal behavior. The reduced order electrochemical model, which is approximated from the pseudo-two-dimensional (P2D) electrochemical model using a Padé approximation method, computes the variation of electrochemical variables and heat generation terms. Simultaneously, a coupled thermal model computes the temperature distribution in the radial direction of the cell. The results from DET model compare favorably to those obtained from solving the 1D radial coupled degradation-electrochemical-thermal partial differential equations in COMSOL Multiphysics, however the DET model returns these results in significantly reduced computational times. Importantly, the model capability in providing insightful information of cell degradation and temperature in a computationally efficient manner paves the way for the health-conscious, real-time optimal control of large format cylindrical cells.